Narodno radikalno dijaštvo - Gantar Godina, Irena (Zgodovinski časopis, 1982)
The author presents the development, aims and the decay of the non-party National-radical pupils (1904-1914) their main principles/views, which they published in their magazine Omladina (1904-1914). Their principles were mainlybased on Czech and T. G. Masaryk's principles, respectively.
Keywords: Narodna napredna stranka; narodni radikali; narodnostno vprašanje; national issue; national radicals; obdobje pred prvo svetovno vojno; Omladina (periodika); political history; politična zgodovina; pre-First World War period; Slovenci; Slovenes